Monopoly - Wolfram Kempe (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1996)
This is the first chapter of a graduate text entitled Topics in Microeconomics. It covers the basics of monopoly theory. Most of the material is kept at an intermediate level to serve as a bridge between the intermediate level training and the graduate level focus of the book. However, some sections, identified with a *, are at an advanced level. The Chapter begins with the simple economics of Cournot monopoly, adding the quality dimension, the assessment of the welfare loss of monopoly in the face of rent seeking behavior, and the dynamics of pricing and inventory when demand is subject to unpredictable fluctuations. Turning to price discrimination, the distinction between first-, second-, and third-degree price discrimination is introduced. The incomplete information theory of second-degree price discrimination is worked out, first for two and then for a continuum of customer types. Next, it is shown how the frequently observed intertemporal price discrimination gives rise to a time consistency problem (durable goods monopoly), and how the basic theory of third-degree price discrimination needs to be modified accordingly. The Chapter closes with the noncooperative bargaining theory of bilateral monopoly and suggests a further marriage of monopoly and bargaining theories. The regulation of monopoly is covered in the separate Chapter on Regulation of Monopoly which was already circulated as a Discussion Paper.
urn:nbn:de:kobv:11-10063596
Keywords: 330